Closing the loop: crop yield response and soil health implications of human excreta-derived fertilizer application in dryland agriculture - Musazura, William; Nkomo, Nqobile; Otieno, Benton; Badza, Taruvinga; Odindo, Alfred Oduor; Ojwach, Steven O. (Frontiers in Sustainable Food Systems, 2025)
IntroductionHuman excreta-derived fertilizers, such as sewage sludge-based co-compost and urine, offer a potential pathway to improve soil fertility and crop productivity in dryland agriculture while promoting circular bioeconomy practices. However, their agronomic performance and environmental safety remain underexplored.MethodsA six-month field experiment was conducted at the Bishopstowe Agricultural Living Lab using a randomized complete block design with five treatments (urine, urine + co-compost, chicken manure, no fertilizer, and conventional fertilizer) and four replications. Chili (Capsicum annuum) yield, soil nitrogen dynamics (mineralization, ammonium, nitrate), enzyme activities (urease, β-glucosidase, phosphatases), microbial communities, soil carbon fractions, and groundwater contamination risks (Escherichia coli, nitrate) were assessed.ResultsChili yield, soil N mineralization, ammonium and nitrate concentrations, enzyme activities, microbial community composition, and active carbon did not differ significantly across treatments (p > 0.05). In contrast, organic carbon and extractable phosphorus were significantly higher in the urine + co-compost and chicken manure treatments. Although co-compost contained high organic carbon, associated microbial activity was lower than that observed with chicken manure. Groundwater contamination by E. coli and nitrate was not significantly affected by excreta-derived amendments during the trial period.Discussion and ConclusionExcreta-derived amendments enhanced soil organic carbon and phosphorus without compromising groundwater quality, highlighting their potential role in resilient and sustainable food systems. Nevertheless, their safe use requires management practices such as salinity control and adherence to WHO sanitation guidelines. The study was limited by its short duration and single-site scope; therefore, long-term (>2 years) and multi-location trials are recommended to fully assess agronomic, soil health, and environmental outcomes of excreta-derived fertilizers in dryland agriculture.